Risk-Taking Behaviors of Adult Bedridden Patients in Neurosurgery: What Could/Should We Do? - Lemaire, Jean-Jacques; Chaix, Rémi; Sontheimer, Anna; Coste, Jérôme; Cousseau, Marie-Anne; Dubois, Charlène; San Juan, Mélanie; Massa, Christelle; Raynaud, Sandrine; Usclade, Alexandra; Pontier, Bénédicte; El Ouadih, Youssef; et al. (Frontiers in Medicine, 2021)
Risk-taking behaviors of adult bedridden patients in neurosurgery are frequent, however little analyzed. We aimed to estimate from the literature and our clinical experience the incidence of the different clinical pictures. Risk-taking behaviors seem to be more frequent than reported. They are often minor, but they can lead to death, irrespectively of the prescription of physical or chemical constraints. We also aimed to contextualize the risks, and to describe the means reducing the consequences for the patients. Two main conditions were identified, the loss of awareness of risk-taking behaviors by the patient, and uncontrolled body motions. Besides current experience feedback analyses and new technological solutions, non exclusive, could limit the complications, while improving the prevention with wearable systems, neighborhood sensors or room monitoring and service robots. Further research is mandatory to develop efficient and reliable systems avoiding complications and saving lives. Ethical and legal issues must also be accounted, notably concerning the privacy of patients and caregivers.